Evidence of energy-, recombination-, and photon-limited escape regimes in giant planet H/He atmospheres - Lampón, Manuel; López-Puertas, M.; Czesla, Stefan; Sánchez López, Alejandro; Lara, L. M.; Salz, M.; Sanz-Forcada, J.; Molaverdikhani, Karan; Quirrenbach, Andreas; Pallé, E.; Caballero, José A.; Henning, Thomas; et al. (Astronomy and astrophysics, 2021)
Hydrodynamic escape is the most efficient atmospheric mechanism of planetary mass loss and has a large impact on planetary evolution. Three hydrodynamic escape regimes have been identified theoretically: energy-limited, recombination-limited, and photon-limited. However, no evidence of these regimes had been reported until now. Here, we report evidence of these three regimes via an analysis of a helium I triplet at 10 830 Å and Lyα absorption involving a 1D hydrodynamic model that allows us to estimate hydrogen recombination and advection rates. In particular, we show that HD 209458 b is in the energy-limited regime, HD 189733 b is in the recombination-limited regime, and GJ 3470 b is in the photon-limited regime. These exoplanets can be considered as benchmark cases for their respective regimes.